The role of TPLs in innovative logistics solutions in importation - Alessandra Vitorino Razzera; Marcelo André Machado (Innovation & Management Review, 2018)
Purpose: The purpose of this paper is to investigate the role of third-party logistics providers (TPLs) in providing innovative logistics solutions for Brazilian importations. Design/methodology/approach: A multiple case study has been conducted in which four logistics service providers are interviewed on the topic of innovation in importation logistics. The collected data (interviews, brochures and presentations) were triangulated and analyzed. Findings: The collected data highlight the integrating role of TPLs in providing innovative logistics solutions of the technological nature, in addition to drivers, which involve communication, trust, logistics and institutional actions. Research limitations/implications: This study, instead of focusing on procedural issues, intended to focus on two important theoretical and practical drivers: innovation in the importation process and strengthening of intangible factors. It is known that trading conditions and geographical proximity have an impact in importation, but they have not been discussed here because of the subject delimitation of the present study. Regarding the implications of the present study, no specific theoretical reference has been found on the subject in terms of the importation process but is rather related to information technology, which is then presented. Practical implications: This study focuses on the fundamental role of TPLs in the development of innovative logistics solutions in importation. Social implications: The fundamental role of TPLs in the development of innovative logistics solutions in importation is based on trust and relationship, internal and external to the organization. Originality/value: This study, instead of focusing on procedural issues, intends to focus on two important theoretical and practical drivers - innovation in the importation process and strengthening of intangible factors - suggesting that a change of mind-set and a differentiated background in importation logistics are developed by TPLs.
Keywords: 650; Innovation; Logistics; Third-party logistics; Supply chain; International logistics; Brazilian importation